Unveiling the Need of Synonym in Code Mixing in the Movie ‘Yowis Ben Finale’ - Dwi Putri Fatmawati; Dyah ‘Ainun Rohimah; Efazetta Fazafaza; Jaizah Nasywa; Teguh Sarosa (Universitas Sebelas Maret, 2024)
This study aims to analyze the internal, external, and factors that arise through the use of code-mixing by the players of the film